The Analysis of English Eduation Abstract at the Islamic Institute of Bengkulu on the Content, Organisation and Language - Endang Haryanto (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
AbstractTheses and journals are several kinds of writing which contain abstract. Thesis is used in educational area, especially in university, as a requirement in completing an academic degree. As one of the most important thesis part is called abstract. The use of abstract is essential in some scientific works, online research, directory, seminar, and call paper. In IAIN Bengkulu, students are obliged to write an abstract as an integral part of their theses. Because of its importance, abstract must be written using the correct form and following the rule of abstracting.This study used descriptive qualitative research. It describes how the students write an abstract based on the rule. As a result, the researcher found some errors on the students’ abstract in terms of organization, content, and language. In addition, the researcher found many grammatical errors. Students also tended to make mistake related to the standard form of abstract. Thus, the researcher knows that most of students’ abstracts still do not follow the rule of composing their abstract.